Correlates of Non-fatal, Opioid Overdose among Women Who Use Opioids in Dar es Salaam, Tanzania. (1st January 2021) - Saleem, Haneefa T.; Likindikoki, Samuel; Nonyane, Bareng A.S.; Haruna Nkya, Iddi; Zhang, Leanne; Mbwambo, Jessie; Latkin, Carl
Highlights: Prevalence of overdose was 34% in a sample of women who use opioids in Tanzania. Injecting drugs, alcohol use, and sleeping outside are associated with overdose. Ever trying to stop heroin use and depression are also associated with overdose. There is a need for overdose surveillance efforts in Tanzania. Abstract: Background: As opioid overdoses and deaths increase globally, little is known about these dimensions in Sub-Saharan Africa. In this paper, we explore factors associated with opioid overdose experiences among a sample of women who use opioids in Dar es Salaam, Tanzania. Methods: We conducted a cross-sectional survey with 200 women who use opioids in Dar es Salaam, Tanzania, recruited via respondent-driven sampling. We fitted unadjusted and adjusted log-binomial regression models with robust standard errors to examine associations between participant characteristics and reporting ever had an opioid overdose in terms of prevalence ratios. Results: Thirty-four percent (n = 68) of participants reported having ever had an opioid overdose. In the final adjusted model, having ever attempted to stop using heroin (adj. PR = 1.46, 95% CI: 1.01-2.12), sleeping outside in the past 6 months (adj. PR = 1.93, 95% CI: 1.29-2.91), injecting drugs (adj. PR = 1.78, 95% CI: 1.19-2.66), alcohol use (adj. PR = 1.56, 95% CI: 1.09-2.23), and having moderately severe to severe depression (adj. PR = 3.10, 95% CI: 1.07-8.97) were all found to be significantly associated with having ever had an opioid overdose. Conclusions: We demonstrate factors associated with opioid overdose among women who use drugs in Tanzania that may not be addressed with injection-focused harm reduction efforts. Our findings suggest the need for overdose surveillance efforts and further work to characterize overdose risks in this context in order to design relevant, targeted interventions to prevent opioid overdose in sub-Saharan Africa.